Pengaruh Kualitas Pelayanan dan Fasilitas Terminal Keberangkatan terhadap Kepuasan Penumpang di Bandar Udara Sultan Muhammad Salahuddin Bima - Tri Nofiyati (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The purpose of this study was to determine whether the influence of service quality and departure terminal facilities on passenger satisfaction at Sultan Muhammad Salahuddin airport, Bima. The type of research taken is quantitative. The source of this research data is primary data that comes from distributing questionnaires with 50 samples, namely passengers who have traveled via air transportation at Sultan Muhammad Salahuddin Airport, Bima. This research uses Multiple Linear Regression analysis method. The results obtained from this study indicate that: (1) H1 service quality has a significant effect on passenger satisfaction at Sultan Muhammad Salahuddin Airport Bima (2) H2 available facilities have a significant effect on passenger satisfaction at Sultan Muhammad Salahuddin Airport Bima. Keywords: Service, Facilities and Passenger Satisfaction.